DIGITAL TECHNOLOGIES FOR FUTURE BIOLOGY TEACHERS STAGES OF ADAPTATION TO COMPETENCIES - YESMAKHANOVA, ZH. SH.; SUMATOKHIN, S.V.; ZHUSSIPOVA, G.Т. (Pedagogy and Psychology, 2025)
DEVELOPING DIGITAL COMPETENCE IN FUTURE TEACHERS THROUGH BLENDED LEARNING APPROACHES This article examines key aspects of training future teachers, focusing on the challenges of digitalizing education, the integration of digital competence, and pedagogical teaching methods. The study’s article selection aimed to provide comprehensive coverage, utilizing the Web of Science database through a university library system. Keywords like «education,» «innovation,» and «digital competence» were used to find relevant research across various fields. The article’s relevance stems from modern society’s demand for well-qualified specialists in general education institutions. Future teachers must not only acquire vast knowledge but also apply it effectively in real-world scenarios. The curriculum for the 6B01505 «Biology Teacher Training» program, including the «Methods of Teaching Biology» course, is designed to incorporate new technologies and teaching methods that engage students and enhance their competencies. To support digital education, the MOODLE platform is used for developing materials such as presentations and video lectures, which align with the course objectives. Additionally, the article explores the role of educational platforms in facilitating effective lesson management and evaluates their services and impact on student learning.